Answer:
y = -4x +2
Explanation:
The slope-intercept form of the equation for a line is conveniently found from the point-slope form. In either case, you need to know the slope. That is ...
... slope = m = (change in y)/(change in x)
For the first two points, the slope is ...
... m = (-6 -(-2))/(2 -1) = -4
Using the point-slope equation for slope m and point (h, k) written as ...
... y = m(x -h) +k
we can substitute m = -4 and (h, k) = (1, -2) to get ...
... y = -4(x -1) -2
... y = -4x +2 . . . . . . . simplify